Revisión de la estimulación del pensamiento lógico mediante el programa OBM en el rendimiento escolar de las matemáticas - Vicuña Peri, Luis Alberto (2003)
The present investigation has like intention, to verify if the program of stimulation for the basic operations logics for the learning of the mathematical one still has use, since the original investigation I am made in 1983 with students of the first year of secondary, of normal intellectual coefficient, without indicators of cerebral organic injury, the present to start off that continuous the high rates of students disapproved in the subject of mathematical, we have believed pertinent, to carry out a revision of the program arrives mentioned but this time extending the cover sample, students of the first a fifth of secondary, without greater control of variables than to be registered student and in conditions of regularity, this modification it does with the intention to verify it the manual works in the conditions of classroom where the participants vary in their degrees of homogeneity. For which the test of basic operations for the learning of the mathematical one was applied to them, which it throws five results: inclusion, classification, serialization, invariance and numerical interpretation in addition count on a record, soon to the experimental group the stimulation was applied to them systematically and to finish was verified: first which indeed the operations stimulated logics are increased in comparison with the group control, and second, the experimental group that increase his performance in the basic operations logics significantly increases the scholastic yield in the mathematical one.